Rancang Bangun Alat Ukur Jarak dengan Sensor Ultrasonik untuk Pesawat Sinar-X Mobile - Muhammad Erfansyah; Budi Santoso; Puji Hartoyo (Poltekkes Kemenkes Semarang, 2023)
Background: Many mobile X-ray aircraft currently do not have meters to measure the distance from the x-ray source to the patient, this makes it very difficult for a radiographer to adjust the position and distance correctly. Currently, there is still a need to develop more efficient and accurate distance measuring tools to support Mobile X-ray Aircraft maintenance.Methods: This research is experimental, making a distance measuring instrument using an ultrasonic sensor with the help of a microcontroller.Results: The device is applied for measuring the distance horizontally and vertically from 90 cm up to 130 cm. Step wisely from 90 cm to 130 cm at incrementally 10 cm. This device will be installed in the tube x-ray mobile device. Comparison is made for the distance in the vertical position of timed by the device to the measured distance using standard technique deviations more less then 0.044 % and in the horizontal 0.036.Conclusions: This concludes that the results obtained sufficiently by the device are accurate and can be recommended for x-ray mobile device accessory.